Laparoscopic Transperitoneal Approach for Vesicovaginal Fistula Repair: the First Experience - Santoso, Jumadi (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To report our first experience in transperitoneal laparoscopic repair of vesicovaginal fistula in Dr. Hasan Sadikin Hospital. Method: A 31-year-old female presented with vesicovaginal fistula after cesarean section. Patient complained of urinary incontinence since 5 years ago. After a failed trial of conservative treatment with catheter drainage, a transperitoneal laparoscopic repair was performed. Initially, cystoscopy was performed to confirm the fistula location and for bilateral ureteric catheterization. A 4-port technique was performed with the patient in lithotomy position and slightly Trendelenburg. Without opening the bladder, the fistula tract was excised and the bladder was separated from the anterior vaginal wall. Both the bladder and vaginal walls were then closed separately using intracorporeal suturing, interposed with the omentum. Result: Total operative time was 270 minutes. Normal diet was resumed on day 1, drain was removed on the first day after surgery, and the patient was discharged on the second day with an indwelling catheter. Surgical wound showed good cosmetic result and no leakage was identified from cystogram after 2 weeks. The catheter was removed after 2 weeks. Conclusion: Laparoscopic transperitoneal repair of vesicovaginal fistula with omentum inteposition is feasible in Dr. Hasan Sadikin Hospital with good outcome, short hospital stay, and good cosmetic result. [Indones J Obstet Gynecol 2014; 4: 223-225] Keywords: laparoscopy, vesicovaginal fistula